Analisis Teori Planned Behavior Terhadap Intensi Menurunkan Berat Badan: Studi Kasus Pada Individu Obesitas Kelas 2 - Muhamad Agung Wijoyo; Citrawanti Oktavia (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Class 2 obesity is a condition characterized by a body mass index (BMI) ≥ 30 and is associated with a high risk of non-communicable diseases such as diabetes mellitus, hypertension, and cardiovascular disease. This study aims to explore the factors influencing weight loss Intention among individuals with type 2 obesity, using the framework of the Theory of Planned Behavior (TPB). A qualitative case study approach was employed, focusing on subject “D,” a 30-year-old adult male weighing 150 kg. Data were collected through in-depth interviews and analyzed based on the TPB components: Attitude toward the Behavior, Subjective Norms, and Perceived Behavioral Control. The findings reveal that although D possesses knowledge regarding the benefits of weight loss and receives support from his family, economic pressures and job instability serve as major barriers to forming a clear Intention to lose weight. Subjective Norms paradoxically contribute to psychological stress, while D’s Perceived Behavioral Control is undermined by the necessity to prioritize job-seeking efforts. These results indicate that Intention is influenced not only by internal motivation but also by the individual’s broader social and economic context.